Longitudinal Assessment of Multiple Sclerosis with the Brain‐Age Paradigm. Issue 1 (6th May 2020) - Cole, James H.; Raffel, Joel; Friede, Tim; Eshaghi, Arman; Brownlee, Wallace J.; Chard, Declan; De Stefano, Nicola; Enzinger, Christian; Pirpamer, Lukas; Filippi, Massimo; Gasperini, Claudio; Rocca, Maria Assunta; et al.
Abstract : Objective: During the natural course of multiple sclerosis (MS), the brain is exposed to aging as well as disease effects. Brain aging can be modeled statistically; the so‐called "brain‐age" paradigm. Here, we evaluated whether brain‐predicted age difference (brain‐PAD) was sensitive to the presence of MS, clinical progression, and future outcomes. Methods: In a longitudinal, multicenter sample of 3, 565 magnetic resonance imaging (MRI) scans, in 1, 204 patients with MS and clinically isolated syndrome (CIS) and 150 healthy controls (mean follow‐up time: patients 3.41 years, healthy controls 1.97 years), we measured "brain‐predicted age" using T1‐weighted MRI. We compared brain‐PAD among patients with MS and patients with CIS and healthy controls, and between disease subtypes. Relationships between brain‐PAD and Expanded Disability Status Scale (EDSS) were explored. Results: Patients with MS had markedly higher brain‐PAD than healthy controls (mean brain‐PAD +10.3 years; 95% confidence interval [CI] = 8.5–12.1] versus 4.3 years; 95% CI = 2.1 to 6.4; p < 0.001). The highest brain‐PADs were in secondary‐progressive MS (+13.3 years; 95% CI = 11.3–15.3). Brain‐PAD at study entry predicted time‐to‐disability progression (hazard ratio 1.02; 95% CI = 1.01–1.03; p < 0.001); although normalized brain volume was a stronger predictor. Greater annualized brain‐PAD increases were associated with greater annualized EDSS score (r = 0.26; p < 0.001). Interpretation: The brain‐age paradigm is sensitive to MS‐related atrophy and clinical progression. A higher brain‐PAD at baseline was associated with more rapid disability progression and the rate of change in brain‐PAD related to worsening disability. Potentially, "brain‐age" could be used as a prognostic biomarker in early‐stage MS, to track disease progression or stratify patients for clinical trial enrollment. ANN NEUROL 2020 ANN NEUROL 2020;88:93–105